Effects of early pregnancy on expression of interferon‐stimulated gene 15, STAT1, OAS1, MX1, and IP‐10 in ovine liver. (24th April 2020) - Yang, Ling; Li, Ning; Zhang, Leying; Bai, Jiachen; Zhao, Zimo; Wang, Yujiao
Abstract: Interferon‐tau (IFNT) regulates maternal recognition during early pregnancy in ruminants. The liver can serve as a hematopoietic organ, and it has immune functions. This study hypothesized whether mRNA and proteins of interferon‐stimulated genes (ISGs) induced by early pregnancy are upregulated in maternal liver. Therefore, we determined the expression of interferon‐stimulated gene 15‐kDa protein (ISG15), 2', 5'‐oligoadenylate synthetase 1 (OAS1), myxovirus resistance protein 1 (MX1), interferon‐gamma‐inducible protein 10 (IP‐10), and signal transducer and activator of transcription 1 (STAT1) in maternal livers during early pregnancy in sheep. Ovine livers were sampled on day 16 of the estrous cycle, and days 13, 16, and 25 of pregnancy, and expression of ISGs was detected by quantitative real‐time PCR, Western blot, and immunohistochemistry analysis. Our results showed that there were increases in expression of the mRNA and proteins of ISG15, OAS1, IP‐10, STAT1, and MX1 during early pregnancy. STAT1 protein was limited to the hepatocytes, and endothelial cells of proper hepatic arteries and hepatic portal veins. In conclusion, the upregulation of ISG15, OAS1, IP‐10, STAT1, and MX1 proteins may be implicated in maternal hepatic immune adjustment and other functions during early pregnancy in sheep.